2002
DOI: 10.1002/jbm.10266
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of chemically treated ostrich pericardium subjected to uniaxial tensile testing: influence of the suture

Abstract: The mechanical behavior of sutured ostrich pericardium was studied by uniaxial tensile testing. One hundred forty-four tissue specimens were assessed: 96 sutured samples (48 in which a centrally located suture was placed at an angle of 90 degrees with respect to the longitudinal axis, whereas in the remaining 48, a centrally located suture was placed at a 45 degrees angle to the longitudinal axis, in sets of 12 samples each, sewn with sutures made of Gore-Tex, nylon, Prolene, or silk), and 48 unsutured control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The need for new, safe bioprostheses requires the in‐depth study of the mechanical behavior of the biomaterial employed as well as its microstructure and the changes it undergoes when subjected to dynamic forces (11). It would also appear to be important to continue research with novel biomaterials that might guarantee greater mechanical resistance (19) and, finally, with innovative systems for the early detection of valve failure, such as the implantation of microsensors and nanofibers that could transmit the slightest variation in the hemodynamic behavior of a cardiac valve leaflet to an external receiver (20).…”
Section: Discussionmentioning
confidence: 99%
“…The need for new, safe bioprostheses requires the in‐depth study of the mechanical behavior of the biomaterial employed as well as its microstructure and the changes it undergoes when subjected to dynamic forces (11). It would also appear to be important to continue research with novel biomaterials that might guarantee greater mechanical resistance (19) and, finally, with innovative systems for the early detection of valve failure, such as the implantation of microsensors and nanofibers that could transmit the slightest variation in the hemodynamic behavior of a cardiac valve leaflet to an external receiver (20).…”
Section: Discussionmentioning
confidence: 99%
“…The literature is mainly focused on examination of mechanical behaviour of sutured biological materials for cardiac bioprostheses, with leading contributions by Garcia Paez at al. [18][19][20][21][22][23][24]. There are no reports on tensile testing of sutured synthetic materials for soft polymeric cardiac prosthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, initial experimental studies demonstrated its high degree of resistance to rupture, tolerance to the suture, and acceptable homogeneity in terms of sample procurement and results. 1,2 On the other hand, current experience in the use of adhesives in medicine, and specifically in the field of cardiovascular surgery, is very limited. Their utilization in inert tissues, such as bioprostheses or implants, raises fundamental questions with regard to their mechanical resistance and stability over time.…”
Section: Introductionmentioning
confidence: 99%